AppCal as support in the calculation of basic feasible solutions to transport problems in the teaching-learning process of linear programming - Leyva, Amado A.; Carreno, Monica; Estrada, Italia; Sandoval, Andres; Carreno, Miriam; Espinoza, German (2016 XI Latin American Conference on Learning Objects and Technology (LACLO), 2016)
New technologies allow to carry out a change in the way we educate more focused on the student rather than the teacher. In this regard, with the support of Information and Communications Technology (TIC) is very common nowadays, students are increasingly using their mobile devices in the classroom, becoming the best friend student, figuratively. Based on the above drawing these guidelines, this paper presents the development of an App for calculating basic feasible solutions to transport problems to support the teaching-learning process to be used inside and outside the classroom; this app is to provide a learning environment movement to transport problems in Linear Programming (PL).